Leptin Interferes with the Effects of the Antiestrogen ICI 182,780 in MCF-7 Breast Cancer Cells - Garofalo, Cecilia; Sisci, Diego; Surmacz, Eva (Clinical cancer research, 2004)
Purpose: Obesity is a risk factor for breast cancer development in postmenopausal women and correlates with shorter disease-free and overall survival in breast cancer patients, regardless of menopausal status. Adipose tissue is a major source of leptin, a cytokine regulating energy balance and controlling different processes in peripheral tissues, including breast cancer cell growth. Here, we investigated whether leptin can counteract antitumorigenic activities of the antiestrogen ICI 182,780 in breast cancer cells. Experimental Design: Mitogenic response to leptin and the effects of leptin on ICI 182,780-dependent growth inhibition were studied in MCF-7 estrogen receptor α-positive breast cancer cells. The expression of leptin receptor and the activation of signaling pathways were studied by Western immunoblotting. The interference of leptin with ICI 182,780-induced estrogen receptor α degradation was probed by Western immunoblotting, fluorescence microscopy, and pulse-chase experiments. Leptin effects on estrogen receptor α–dependent transcription in the presence and absence of ICI 182,780 were studied by luciferase reporter assays and chromatin immunoprecipitation. Results: MCF-7 cells were found to express the leptin receptor and respond to leptin with cell growth and activation the signal transducers and activators of transcription 3, extracellular signal-regulated kinase-1/2, and Akt/GSK3/pRb pathways. The exposure of cells to 10 nmol/L ICI 182,780 blocked cell proliferation, induced rapid estrogen receptor α degradation, inhibited nuclear estrogen receptor α expression, and reduced estrogen receptor α–dependent transcription from estrogen response element–containing promoters. All of these effects of ICI 182,780 were significantly attenuated by simultaneous treatment of cells with 100 ng/mL leptin. Conclusions: Leptin interferes with the effects of ICI 182,780 on estrogen receptor α in breast cancer cells. Thus, high leptin levels in obese breast cancer patients might contribute to the development of antiestrogen resistance.